Peran Sistem Informasi Manajemen Dalam Keberhasilan E-Business - Mega Yuwanda; Rayyan Firdaus (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Right now, the utilization of data and correspondence innovation fundamentally affects different business areas, including producing. One arising idea is e-business, otherwise called electronic business. This idea underlines data exchanging and paperless exchanges through different innovations like Electronic Trade of Data (EDI), email, electronic notice sheets, electronic assets move, and other organization based propels. An e-business data framework is a gadget, innovation, or system that uses equipment, programming, organizations, and human insight to interface, do exchanges, and complete different hierarchical exercises without being restricted by time or area. The utilization of e-business data frameworks is a significant instrument that associations use to further develop business activities at the nearby and worldwide level. Indonesia is one of the trailblazers in web-based business and internet business. Nonetheless, the potential presented by e-business haven't completely taken advantage of by business affiliations.